Hydrogen Sulfide Regulates Salt Tolerance in Rice by Maintaining Na+/K+ Balance, Mineral Homeostasis and Oxidative Metabolism Under Excessive Salt Stress - Mostofa, Mohammad G.; Saegusa, Daisuke; Fujita, Masayuki; Tran, Lam-Son Phan (Frontiers in Plant Science, 2015)
Being a salt sensitive crop, rice growth and development are frequently affected by soil salinity. Hydrogen sulfide (H2S) has been recently explored as an important priming agent regulating diverse physiological processes of plant growth and development. Despite its enormous prospects in plant systems, the role of H2S in plant stress tolerance is still elusive. Here, a combined pharmacological, physiological and biochemical approach was executed aiming to examine the possible mechanism of H2S in enhancement of salt stress tolerance in rice. We show that pretreating rice plants with H2S donor sodium bisulfide (NaHS) clearly improved, but application of H2S scavenger hypotaurine with NaHS decreased growth and biomass-related parameters under salt stress. NaHS-pretreated salt-stressed plants exhibited increased chlorophyll, carotenoid and soluble protein contents, as well as suppressed accumulation of reactive oxygen species (ROS), contributing to oxidative damage protection. The protective mechanism of H2S against oxidative stress was correlated with the elevated levels of ascorbic acid, glutathione, redox states, and the enhanced activities of ROS- and methylglyoxal-detoxifying enzymes. Notably, decreased uptake of Na+, decreased Na+/K+ ratio and balanced mineral contents indicated a role of H2S in ion homeostasis under salt stress. Altogether, our results highlight that modulation of the level of endogenous H2S genetically or exogenously could be employed to attain better growth and development of rice, and perhaps other crops, under salt stress. Furthermore, our study reveals the importance of the implication of gasotransmitter like H2S for the management of salt stress, thus assisting rice plants to adapt to adverse environmental changes.